IMPROVING THE APPLICATION OF DIGITAL TECHNOLOGIES IN THE HIGHER EDUCATION SYSTEM (Marketing Journal, 2025)
This article analyzes the use of digital technologies in the higher education system and their impact on the educational process. Ways to improve digital infrastructure, improve teachersʼ skills, and effectively use interactive learning methods were consid ered. The importance of digital learning platforms, artificial intelligence and blockchain technologies were also discussed. The results show that digital technologies are an important tool in improving the quality of education.
Keywords: digital learning; artificial intelligence; distance learning; blockchain; online platform; interactive learning; digital infrastructure; personalized learning